The Multifaceted Impact of Erasmus Programme on the School-to-Work Transition: A Matching Sensitivity Analysis - Croce, Giuseppe; Ghignoni, Emanuela (Research in higher education, 2024)
This study investigates the effects of studying abroad through the Erasmus Programme (EP), a European Union programme launched primarily to foster international mobility and cultural exchange of University students, on the school-to-work transition of university graduates. Since a satisfactory transition does not only mean finding a job, but also concerns the wage level and the quality of work, such as stability, working hours and risk of overeducation, we consider all these aspects in order to draw a comprehensive picture of the effect of the EP. We exploit a composite dataset, built on administrative and survey data, covering all graduates from the largest Italian university from 2011 to 2015, and replicate the analysis on a national sample of graduates to verify whether the results can be extended nationwide. Estimates are provided, based on a PSM procedure, of the effects of the EP on the probability of employment, including abroad, on the quality of jobs and on wage levels at different points in time after graduation. We also investigate whether less advantaged students benefit from the Erasmus experience, and provide insights about the role of the foreign languages skills. The results show that the participation in the EP improves employment prospects at least in the short term, as well as the quality of job, and has a positive long term effect on the participants' ability to find a job abroad. The wages of participants are persistently higher than those of non-participants. Less advantaged groups also benefit from the Erasmus experience.